Compras públicas ambientalmente sustentáveis em um contexto de green supply chain management: um survey sobre o papel do treinamento ambiental, empowerment dos funcionários e fatores influenciadores externos - Izar, Alberto Luiz Toffano [UNESP] (2015)
The objective of this study is to investigate the level of influence of environmental training and empowerment of employees to adopt environmentally sustainable procurement in public universities in Brazil. For this, a theoretical grounding was held to discuss issues relating to existing legal instruments in Brazil for environmentally sustainable public procurement, environmental criteria that can be used in public procurement, the profile of those responsible for public procurement department, and identify drivers and barriers to the environmentally sustainable procurement. This theoretical grounding supported the develpment of an empirical research, which was collected from 52 procurement department, for further analysis and processing by using descriptive statistics and correlation. The result show: (a) the departments of the sample indicate that many practices/ initiative are being implemented to enable the sustainable procurement are receiving training and have autonomy to pursue sustainable procurement; (c) Environmental Laws has become more demanding, however, they are still very insufficient according to the view of those responsible for purchasing, unable to generate awareness in the population; (d) while the green supply chain management in the private sector is already showing good results, the public sector has shown incipient, highlighting a state with much difficulty creating synergy with its suppliers and consumers. The originality of this research is the fact, to date, has not been found similar research on environmental training, empowerment, external factors and adopting sustainable procurement practices in the Brazilian context. Both managers and stakeholders can learn from this work and plain strategies to assist the achievement of sustainable results